PERBANDINGAN PENGGUNAAN TEKNIK JAHIT DAN TEKNIK OBRAS BULU MATA PALSU PADA HASIL TATA RIAS MATA SIPIT PENGANTIN INTERNASIONAL - Santri Indah Mayangsari; Nieke Andina Wijaya; Maspiyah; Nia Kusstianti (Jurnal Tata Rias, 2026)
False eyelashes are an essential part of international bridal eye makeup, especially for brides with narrow or monolid eyes, as they help produce a more open, expressive, and well-balanced appearance. A range of application methods is available, including the stitching and overlock techniques. The choice of method significantly affects the final makeup outcome in terms of aesthetics, comfort, and durability. This study investigates the differences in eye-makeup results for international brides with narrow eyes using stitching and overlock techniques, focusing on smoothness, symmetry, harmony with the overall eye look, accuracy of application, and neatness. Employing an experimental design with a quantitative approach, the research involved 31 respondents. Data were collected through direct observation, written questionnaires, and supporting documentation, then analyzed using mean scores and the Mann–Whitney U test with SPSS 26. The results show that the stitching technique achieved an average score of 3.625 (rated as excellent), while the overlock technique scored 3.510 (also rated as excellent). The Mann–Whitney U analysis produced a non-significant value of 0.265 > 0.05, indicating no statistically significant difference between the two techniques for false eyelash application..Keywords: Sewing Technique, Obras Technique, Slanted eye Make Up